Medical tourism among Indonesians: a scoping review - Gregorius Abanit Asa; Nelsensius Klau Fauk; Caitlan McLean; Paul Russell Ward (BMC Health Services Research, 2024)
Abstract Background International medical travel or medical tourism is not a new phenomenon in many countries, including among Indonesians. Indonesia is reported as a major source of patients from the lower, middle, to upper classes for its neighbouring countries. This scoping review aims to synthesise evidence on supporting factors for Indonesians taking medical tourism and what needs to be improved in Indonesia’s health system. Methods We conducted a scoping review guided by a framework provided by Arksey and O’Malley. We systematically searched existing literature from 5 databases, including MEDLINE, PubMed, Scopus, ProQuest, and Wiley. Data were extracted based on study details, study design, characteristics of participants and results. Analysis followed the three-stage procedure outlined by Thomas and Harden: (1) coding the text line by line, interpreting the data and identifying concepts or themes; (2) developing descriptive themes by grouping similar concepts in theme and subtheme and (3) generating analytical themes by reviewing preliminary themes and discussing the addition or revision of themes. Results A total of 25 articles were included in this review. The review highlights a broad range of facilitators for medical tourism among Indonesians: (i) availability of health services, medical specialities, and person-centred care, (ii) region adjacency, transport, and health agency, (iii) affordability of medical treatment, (iv) religious and socio-cultural factors, and (v) reasons patients reported distrust in Indonesian doctors. Conclusion The findings indicate improvements in the Indonesian health system are necessary if the increasing rates of international medical tourism by Indonesian people are to change. Addressing the factors identified in this scoping review through avenues including policy may increase people’s satisfaction and trust towards health care and treatment in Indonesia, thereby reducing the number of Indonesian people taking medical tourism.